IMPLEMENTASI FUZZY SIMPLE ADDITIVE WEIGHTING DALAM PENILAIAN KINERJA PENYULUH PERTANIAN - Suranti, Dewi; Ikhsan, Mohamad (JIK: Jurnal Ilmu Komputer, 2017)
In order to build qualified and reliable agricultural human resources, it is necessary for professional, creative, innovative and global-oriented Agricultural Extension workers in the provision of productive, effective and efficient counseling. Agricultural Extension is directed to carry out advisory and consultation tasks for the main actors and business actors in developing their agribusiness business, so the adoption of appropriate technology can run well and in turn increase the empowerment of the main actors, productions, productivity, income and welfare of farmers and their families. The performance of agricultural extension workers can be seen in aspects of preparation, implementation, evaluation and reporting, development of agricultural extension and agricultural extension professional development. In addition, agricultural extension programs should be based on analysis of farmers' needs and reflect current conditions. Applying Fuzzy Simple Additive Wighted in appraisal of farmer extension performance in BP3K aims to know the performance of agricultural extension in consultation at UPT BPP Sukaraja. This is due to the lack of extension workers in BP3K Sukaraja. The results of the resulting assessment in the form of work performance ranking of each extension worker. Decision Support System is built to facilitate BP3K in performing accurate assessment of extension worker performance in accordance with the program and work plan that has been made and carried out by agricultural extension either in the preparation stage, implementation, evaluation and self development propofesional.Ã‚Â Keywords : Decision Support System, FSAW, Agricultural performance